(untitled) - Taggart, James H . (New York, 1993)
A broad but economical coverage of all the key aspects of international business strategy, including reviews of the latest contributions to this field. Buzz-words and jargon are demystified within this book in order that the reader can quickly get to the heart of the matter. Examples form UK/Europe/USA/Asia will improve the reader's understanding of corporate decisions in an international context.
Keywords: International economic relations